2007 IEEE International Electron Devices Meeting 2007
DOI: 10.1109/iedm.2007.4419075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TiN Metal gate on NBTI assessed by interface states and fast transient effect characterization

Abstract: In order to address NBTI degradation mechanism on With the decrease of the high-k layer thickness, NBTI high-k stacks, On The Fly measurements from -1.2V to -2V becomes more critical than PBTI. The relative contribution stress voltages with slow recovery at OV were conducted. of interface states and trapping on NBTI is analysed in HfAs detailed by Huard et al [6], linear relations between drain based stacks. Dit density and generation kinetics were found current and VT variations were beforehand extracted (Fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…In fact, enhancement of NBTI by N introduction in the dielectric widely reported in the literature [1][2][3]5] is here confirmed and accurately quantify in the considered technology node. However, the study also revealed that increasing TiN and high-k thicknesses have a beneficial effect on NBTI.…”
Section: A Negative Bias Temperature Instability (Nbti)supporting
confidence: 80%
See 2 more Smart Citations
“…In fact, enhancement of NBTI by N introduction in the dielectric widely reported in the literature [1][2][3]5] is here confirmed and accurately quantify in the considered technology node. However, the study also revealed that increasing TiN and high-k thicknesses have a beneficial effect on NBTI.…”
Section: A Negative Bias Temperature Instability (Nbti)supporting
confidence: 80%
“…NBTI of high-k dielectric stacks is caused by the generation of interface traps (permanent part, field driven [1]) and a hole trapping mechanism (recoverable part, more likely gate voltage dependent [1]) [2,3]. In order to address the impact of the process variations on each of the component, AC stresses that allow complete detrapping have been first used to quantify the permanent part of the degradation (i.e.…”
Section: A Negative Bias Temperature Instability (Nbti)mentioning
confidence: 99%
See 1 more Smart Citation
“…The shift in V T due to the creation of interface defects depends on the applied bias/electric field, temperature (T) and stress time (t), which can be described using an Arrhenius dependence and a power law dependence, respectively [5], leading to Eq. (1).…”
Section: Introductionmentioning
confidence: 99%
“…Proper analysis techniques can provide information on charge trapping [32, 70-74, 81, 83, 85] and the effect on device performance, separation of fast and slow trapping processes [20,32,50,54,55,74,86], and bias temperature instability [50,[87][88][89][90].…”
Section: Applicationsmentioning
confidence: 99%